China's 2008 Labor Contract Law : Implementation and Implications for China's Workers - Gallagher, Mary; Giles, John; Park, Albert; Wang, Meiyan (World Bank, Washington, DC, 2013)
This paper presents empirical evidence from household and firm survey data collected during 2009-2010 on the implementation of the 2008 Labor Contract Law and its effects on China's workers. The government and local labor bureaus have made substantial efforts to enforce the provisions of the new law, which has likely contributed to reversing a trend toward increasing informalization of the urban labor market. Enforcement of the law, however, varies substantially across cities. The paper analyzes the determinants of worker satisfaction with the enforcement of the law, the propensity of workers to have a labor contract, workers' awareness of the content of the law, and their likelihood of initiating disputes. The paper finds that all of these factors are highly correlated with the level of education, especially for migrants. Although higher labor costs may have had a negative impact on manufacturing employment growth, this has not led to an overall increase in aggregate unemployment or prevented the rapid growth of real wages. Less progress has been made in increasing social insurance coverage, although signing a labor contract is more likely to be associated with participation in social insurance programs than in the past, particularly for migrant workers.